339 Long-term Perception of Medication Effectiveness in Subjects Receiving Lemborexant for up to 12 Months. (3rd May 2021) - Drake, Christopher; Yardley, Jane; Pinner, Kate; Perdomo, Carlos; Moline, Margaret
Abstract: Introduction: The Patient Global Impression–Insomnia version (PGI-I) is a self-report instrument used to evaluate a patient's perception of the effects of their insomnia medication on their sleep relative to starting treatment. The PGI-I includes 3 items related to medication effects (helped/worsened sleep; decreased/increased time to fall asleep; and increased/decreased total sleep; responses include: 1=positive, 2=neutral, 3=negative) and 1 item related to perceived appropriateness of study medication strength (responses include: 1=too strong, 2=just right, 3=too weak). In Study E2006-G000-303 (Study 303; SUNRISE-2; NCT02952820), significantly greater percentages of subjects reported a positive impact of the dual orexin receptor antagonist lemborexant (LEM) versus placebo (PBO) at 1, 3, and 6mo for each of the PGI-I items related to medication effects. PGI-I results at 9 and 12mo are presented here for subjects that received continuous treatment with LEM for up to 12mo. Methods: Study 303 was a 12-mo, randomized, double-blind, PBO-controlled (first 6mo [Period 1]), phase 3 study. Subjects were aged ≥18y with insomnia disorder. During Period 1, subjects received PBO (n=318) or LEM (5mg, [LEM5], n=316; 10mg, [LEM10], n=315). During Period 2 (second 6mo), LEM subjects continued their assigned dose while PBO subjects were rerandomized to LEM5 or LEM10 (reported separately). Subjects were also administered the PGI-I at months 9 and 12. Results: At 9 and 12mo, the majority of LEM5 (9mo, n=241; 12mo, n=205) and LEM10 (9mo, n=211; 12mo, n=192) subjects reported that their study medication "helped" sleep at night (9mo: LEM5=73.4%; LEM10=76.3%; 12mo: LEM5=74.6%; LEM10=77.6%), reduced time to fall asleep (9mo: LEM5=79.3%, LEM10=78.2%; 12mo: LEM5=76.6%, LEM10=80.2%), and increased total sleep time (9mo: LEM5=62.2%, LEM10=73.0%; 12mo: LEM5=62.4%; LEM10=65.1%). Also, at both 9 and 12mo, the majority of subjects in the LEM5 and LEM10 groups, responded that treatment strength was "just right" (9mo: LEM5=60.6%, LEM10=62.1%; 12mo: LEM5=63.4%; LEM10=60.4%). LEM was well tolerated. Most adverse events were mild or moderate. Conclusion: The majority of subjects receiving LEM5 or LEM10 reported a positive medication effect at both 9 and 12mo, sustaining similar positive effects for LEM achieved earlier, during the first 6mo of treatment in Study 303. Support (if any): Eisai Inc.